Fostering Religious Character Through Safari Istighotsah: Insights from Islamic Education Practice in Indonesia - Febrianti, Ericka Febrianti; Arifudin, Muhammad; al-Islam, Majid (Interdisciplinary Journal of Social Sciences, 2025)
Religious character is a fundamental aspect of moral development that students greatly need. The cultivation of such character can be achieved through the habituation of specific religious activities. Istighotsah is a spiritual practice conducted to seek help and guidance from Allah SWT. The Safari Istighotsah program at MTs Raden Fatah Driyorejo Gresik consists of a series of structured activities that have the potential to instill religious character among students. This study aims to address the following research questions: How is the Safari Istighotsah implemented in fostering religious character among students at MTs Raden Fatah Driyorejo Gresik? What forms of religious character are developed through the Safari Istighotsah at MTs Raden Fatah Driyorejo Gresik? and What are the supporting and inhibiting factors in the implementation of Safari Istighotsah as an effort to instill religious character in students at MTs Raden Fatah Driyorejo Gresik?. This research employs a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation. The data analysis technique follows the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The validity of the findings was ensured through source triangulation, technique triangulation, and theoretical triangulation. The findings reveal that the Safari Istighotsah program has a positive impact on the development of students' religious character at MTs Raden Fatah Driyorejo Gresik, particularly in fostering respectful behavior towards parents and enhancing students' enthusiasm in learning and practicing religious rituals.